A Meta-analysis Assessing Diarrhea and Pneumonia in HIV-Exposed Uninfected Compared With HIV-Unexposed Uninfected Infants and Children. (1st September 2019) - Brennan, Alana T.; Bonawitz, Rachael; Gill, Christopher J.; Thea, Donald M.; Kleinman, Mary; Long, Lawrence; McCallum, Caitryn; Fox, Matthew P.
Abstract : Objective: Previous studies have demonstrated that HIV-exposed uninfected (HEU) infants and children experience morbidity and mortality at rates exceeding those of their HIV-unexposed uninfected (HUU) counterparts. We sought to summarize the association between HEU vs. HUU infants and children for the outcomes of diarrhea and pneumonia. Design: Meta-analysis. Methods: We reviewed studies comparing infants and children in the 2 groups for these infectious disease outcomes, in any setting, from 1993 to 2018 from 6 databases. Results: We included 12 studies, and 17, 955 subjects total [n = 5074 (28.3%) HEU and n = 12, 881 (71.7%) HUU]. Random-effects models showed HEU infants and children had a 20% increase in the relative risk of acute diarrhea and a 30% increase in the relative risk of pneumonia when compared with their HUU counterparts. When stratifying by time since birth, we showed that HEU vs. HUU children had a 50% and 70% increased risk of diarrhea and pneumonia, respectively, in the first 6 months of life. Conclusions: We show an increased risk of diarrhea and pneumonia for HEU vs. HUU infants and children. Although we acknowledge, and commend, the immense public health success of prevention of mother-to-child transmission, we now have an enlarging population of children that seem to be vulnerable to not only death, but increased morbidity. We need to turn our attention to understanding the underlying mechanism and designing effective public health solutions. Further longitudinal research is needed to elucidate possible underlying immunological and/or sociological mechanisms that explain these differences in morbidity. Abstract : Supplemental Digital Content is Available in the Text.